Pelayanan Permohonan Paspor di Kantor Imigrasi Kelas II Tempat Pemeriksaan Imigrasi Lhokseumawe - Setiawan, Khalil Noverri; Sukmawati, Cut; Nirzalin, Nirzalin (Jurnal Transparansi Publik (JTP), 2024)
This study examines passport application services at the Immigration Office, Class II TPI Lhokseumawe. It is known that the use of the M-Paspor application is still experiencing various problems, especially in the passport application service process, which has changed from manual to using the online system, and problem solving by the Immigration Office. The research focuses on online passport services and problem solving by the TPI Lhokseumawe Class II Immigration Office regarding online passport application services. The theory used to analyze the problem is public service theory. The research method uses a qualitative approach. Data collection techniques include observation, interviews, and documentation. The results showed that the passport application service process at the Immigration Office Class II TPI Lhokseumawe uses two methods, namely walk-in passport services and online through the M-Paspor application. The walk-in passport application process is limited to a quota of 50 per day and is given only to priority people such as senior citizens over 60 years old, infants, breastfeeding mothers, and pregnant women. Whereas passport applications online, namely using the M-Paspor application on mobile phones, have referred to the Minimum Service Standards, including clear service procedures by providing Standard Operating Procedures, fast turnaround times because they have registered in advance through the M-Paspor application, service fees referring to Government Regulation Number 28 of 2019, service products in the form of passports that can be submitted online at this time, complete facilities and infrastructure, as well as maximum competence of service providers. There are problems with the online passport application service at the Immigration Office Class II TPI Lhokseumawe, including the public's understanding of using the M-Paspor application, problematic internet networks, and the M-Passport application system, which is frequently updated. Problem solving is carried out through the stages of reporting complaints from the public, which are followed up through identifying problems by the leadership, giving dispositions to the responsible section, and making decisions to resolve problems related to the service of passport applications by the community.